Beyond the call : the true story of one World War II pilot's covert mission to rescue POWs on the Eastern Front - Trimble, Lee, 1950- (Berkley Caliber, 2015)
"Near the end of World War II, thousands of Allied ex-POWs were abandoned to wander the war-torn Eastern Front, modern day Ukraine. With no food, shelter, or supplies, they were an army of dying men. The Red Army had pushed the Nazis out of Russia. As they advanced across Poland, the prison camps of the Third Reich were discovered and liberated. In defiance of humanity, the freed Allied prisoners were discarded without aid. The Soviets viewed POWs as cowards, and regarded all refugees as potential spies or partisans. The United States repeatedly offered to help recover their POWs, but were refused. With relations between the allies strained, a plan was conceived for an undercover rescue mission. In total secrecy, the OSS chose an obscure American air force detachment stationed at a Ukrainian airfield; it would provide the base and the cover for the operation. The man they picked to undertake it was veteran 8th Air Force bomber pilot Captain Robert Trimble. With little covert training, already scarred by the trials of combat, Trimble took the mission. He would survive by wit, courage, and a determination to do some good in a terrible war. Alone he faced up to the terrifying Soviet secret police, saving hundreds of lives. At the same time he battled to come to terms with the trauma of war and find his own way home to his wife and child. One ordinary man. One extraordinary mission. A thousand lives at stake. This is the compelling, inspiring true story of an American hero who laid his life on the line to bring his fellow men home to safety and freedom. Include photos"--